CRITERIA AND INDICATORS FOR EVALUATING THE PROFESSIONAL ACTIVITY OF BIOLOGY TEACHERS OF GENERAL SECONDARY EDUCATION INSTITUTIONS - Vashchenko, Lidiia (Continuing Professional Education: Theory and Practice, 2025)
This study identifies criteria for evaluating the pedagogical activity of biology teachers in secondary education institutions: informational, subject-based, methodological, motivational, self-educational, learning effectiveness, and self-assessment ability. Indicators have been developed for each of them, which include the main essential features of the criterion. The results of a study of the attitude of biology teachers, as an object of evaluation, to the proposed criteria and evaluation indicators are highlighted. The data were collected using an online survey. It was found that teachers who participated in the survey preferred communicative, subject-based, and methodological criteria for evaluating pedagogical activity. Motivational and informational criteria were underestimated, which took the last two places in the rating of assessments. The results of the study made it possible to draw conclusions about the need to use an integrated approach to assessment when assessing pedagogical skills, when not only the result of pedagogical work is evaluated, but also the process of pedagogical activity itself. This explains the need for further research into the need to move from the practice of assessing general qualities to assessing the components of a teachers’ pedagogical skills when evaluating a teacher’s work.